Correction: Impact of samarium on magnetic and optoelectronic properties of magnesium-based MgSm2X4 (X = S and Se) spinels for spintronics. - Nasir Rahman; Ahmed Azzouz-Rached; Mudasser Husain; Bashar M Al-Khamiseh; Khamael M Abualnaja; Ghaida Alosaimi; Vineet Tirth; Hassan Alqahtani; Ali Algahtani; Tawfiq Al-Mughanam; Soufyane Belhachi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0309388.].